2004
DOI: 10.1074/jbc.m410007200
|View full text |Cite
|
Sign up to set email alerts
|

The Peptide-Substrate-binding Domain of Collagen Prolyl 4-Hydroxylases Is a Tetratricopeptide Repeat Domain with Functional Aromatic Residues

Abstract: Collagen prolyl 4-hydroxylases catalyze the formation of 4-hydroxyproline in -X-Pro-Gly-sequences and have an essential role in collagen synthesis. The vertebrate enzymes are ␣ 2 ␤ 2 tetramers in which the catalytic ␣-subunits contain separate peptide-substrate-binding and catalytic domains. We report on the crystal structure of the peptide-substrate-binding domain of the human type I enzyme refined at 2.3 Å resolution. It was found to belong to a family of tetratricopeptide repeat domains that are involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
56
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(61 citation statements)
references
References 49 publications
5
56
0
Order By: Relevance
“…Many characteristic features of peptide binding to the C-P4Hs can be explained by binding to this domain rather than the catalytic domain (24). This domain has been crystallized and shown to belong to the tetratricopeptide repeat domains and have a groove lined by tyrosines, mutagenesis studies of which indicated that tyrosines 158, 163,193,196,199,230, and 233 are particularly important for peptide binding (25). This region of the P4H-TM sequence shows no similarity to those of the C-P4H ␣ subunits, and none of the seven tyrosines is conserved in the human P4H-TM sequence (Fig.…”
Section: The P4h-tm Sequence Is More Closely Related To the C-p4h Thamentioning
confidence: 99%
“…Many characteristic features of peptide binding to the C-P4Hs can be explained by binding to this domain rather than the catalytic domain (24). This domain has been crystallized and shown to belong to the tetratricopeptide repeat domains and have a groove lined by tyrosines, mutagenesis studies of which indicated that tyrosines 158, 163,193,196,199,230, and 233 are particularly important for peptide binding (25). This region of the P4H-TM sequence shows no similarity to those of the C-P4H ␣ subunits, and none of the seven tyrosines is conserved in the human P4H-TM sequence (Fig.…”
Section: The P4h-tm Sequence Is More Closely Related To the C-p4h Thamentioning
confidence: 99%
“…1C; Pekkala et al 2004). The C-P4H TPR domain is involved in the binding of the [X-Pro-Gly] n triplets from collagen and enhances the activity of the C-P4H catalytic dioxygenase domain (also located within this a subunit) responsible for hydroxylation of the Pro side-chains from collagen.…”
Section: Comparison With Other Tpr Proteinsmentioning
confidence: 99%
“…TPR motifs mediate protein-protein and proteinpeptide interactions, and the assembly of multiprotein complexes (36). The structure of the peptide-substrate-binding domain of human collagen P4H-I, comprising residues 144-244 of the 517-amino-acid (I) subunit, has been recently shown to consist of two TPR motifs and a solvating helix (37). To study whether amino acid differences in the TPR motifs of the C. elegans and C. briggsae PHY polypeptides could explain the differences in their assembly properties, site directed mutagenesis was performed on two separate divergent amino acids in each of the PHY-1 and PHY-2 TPR motifs to change the C .…”
Section: Double Mutagenesis Of the C Elegans And C Briggsae Phy-1 Amentioning
confidence: 99%